Countdown to 2015: State of MDG 4 in India and South Africa - Kuzeeko, Faith; Hornby, Diana; Srinivas, Sunitha (Indian Journal of Pharmacy Practice)
At the International Conference on Primary Health Care in 1978, where the Alma Ata Declaration took place, all global leaders agreed upon achieving eight Millennium Development Goals (MDG) by 2015. This paper focuses on MDG 4, which aimed to reduce under-five deaths by two-thirds by 2015 in each country. In 2008 8.8 million under-five deaths were reported worldwide, of which 40% had occurred during the neonatal period. The main causes are pneumonia, diarrhoea, pre-term birth defects and birth asphyxia, with malnutrition as the underlying cause. WHO further identified the principal determinants that lead to child death as environmental, socio-economic and behavioural factors. It was found that children from poor households of low income, that lack basic sanitation and safe drinking water, were mostly denied their rights to regular access to quality health care. Moreover children whose mothers lacked basic education were less likely to reach the age of five than those whose mothers had basic education. Another challenge faced by global leaders is that one billion children worldwide do not have regular access to essential medicines. In sub-Saharan Africa 1 in 6 children die before they reach the age of five, followed by South Asia where 1 in 7 children die before the age of five. South Africa has made no progress to attaining their goal by 2015, whilst India has made some progress but not significant enough to achieve their goal at the current pace. Other countries have adopted a community-based approach to increase and expand health coverage. South Africa and India can reduce health inequalities by addressing the underlying causes and reducing the gaps that exist. It is also recommended that each government takes it upon themselves to empower all women, to ultimately improve child survival.
Keywords: Millennium Development Goal; Infant mortality; Essential medicines; South Africa; India